Інновації в освіті та основні підходи до їх вивчення - Смерічевська, С. В. (My University, 2006)
Характеризуються особливості процесу становлення інноваційної освіти в Україні на підставі вияву основних підходів до розуміння сутності інновацій в освіті та обґрунтуванні доцільності розмежування понять “інновації в освіті” та “інноваційна освіта”. The features of the process of formation of innovative education in Ukraine are characterized based on the identification of the main approaches to understanding the essence of innovations in education and substantiation of the expediency of distinguishing the concepts of “innovation in education” and “innovative education”.
Keywords: інновації; innovations; освіта; education